Chemical variables - lake from Bolmen, Subbasin West, 2022-05-10–2025-11-27 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2026)
Manual grab samples for chemical analysis are taken from the lake on a biweekly basis during ice-free conditions, and on a monthly basis during ice cover conditions. At the central lake sampling location water samples are collected from both epi- and hypolimnion during periods of stratification.
Bolmen Research Station (2026). Chemical variables - lake from Bolmen, Subbasin West, 2022-05-10–2025-11-27 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/CYbrF5QZ9D8r23AYCuvhpiM-
Keywords: Bolmen Research Station; Lake; Time instant; Time instant; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap